Identification of potential novel proteomic markers of Leishmania spp.-derived exosomes - da Silva Lira Filho, Alonso; Lafleur, Andrea; Marcet-Palacios, Marcelo; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2024)
Extracellular vesicles (EVs) are heterogenous cell-derived membrane-bound structures which can be subdivided into three distinct classes according to distinct morphological characteristics, cellular origins, and functions. While apoptotic bodies and ectosomes are medium to large-sized vesicles, exosomes are the smallest EVsa trait which allows for rapid diffusion and uptake, implicating them as major players in homeostatic functions, health, and disease. Exosome biogenesis occurs through the ESCRT pathway, which is extremely well-conserved throughout most branches of prokarya and eukarya. Exosomes produced by the protozoan parasite Leishmania are key effectors of virulence and drivers of pathogenesis within mammalian hosts. Despite the importance of Leishmania-derived EVs in the immunopathogenesis of leishmaniasis, techniques for the identification of EVs of nonmammalian origin remain inaccurate in comparison to their well-characterized mammalian counterparts. In consequence, we still lack reliable and specific markers for Leishmania-derived exosomes, which poses a significant challenge to the field. Herein, we utilized serial differential ultracentrifugation to separate three distinct fractions of Leishmania-derived EVs and validated their properties using nanoparticle tracking analysis and transmission electron microscopy. Through LC-MS/MS proteomic and bioinformatic analysis, we confirmed the cellular origins of each isolated fraction and identified potential novel protein markers for Leishmania-derived exosomes, including proteins of the ESCRT pathway and the parasitic phosphatase PRL-1. Further investigation is required to determine the specificity and sensitivity of these markers.